1996
DOI: 10.1002/19960401nt3
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic toxic effects of fusarium moniliforme and fumonisin B1 in rats and mice

Abstract: Fumonisins are mycotoxins produced by the fungi Fusarium moniliforme, F. proliferatum, and other Fusarium species. Fumonisin B1, the most commonly found fumonisin, causes the fatal diseases equine leukoencephalomalacia and porcine pulmonary edema. Fumonisins are suspected human carcinogens because of the extraordinarily high incidences of esophageal cancer coincidentally found in areas of southern Africa and China where F. moniliforme-contaminated corn is consumed as a dietary staple. The subchronic (up to 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…Our results were supported by previous studies focused on FB 1 , FB 2 , and FB 3 performed in rats and mice. [1718] But macroscopic examinations did not reveal damage of the kidney of mice treated by FB 1 and FB 1 + DON. However, we think that a prolongation of duration of our experiments in order to show an evident damage of kidney induced by FB 1 and DON tested at very low doses should lead to marked histopathological effects.…”
Section: Discussionmentioning
confidence: 98%
“…Our results were supported by previous studies focused on FB 1 , FB 2 , and FB 3 performed in rats and mice. [1718] But macroscopic examinations did not reveal damage of the kidney of mice treated by FB 1 and FB 1 + DON. However, we think that a prolongation of duration of our experiments in order to show an evident damage of kidney induced by FB 1 and DON tested at very low doses should lead to marked histopathological effects.…”
Section: Discussionmentioning
confidence: 98%
“…Fumonisins are mycotoxins produced by certain strains of Fusarium moniliforme, the most commonly occurring fungi on corn, sorghum, millet and other agricultural products (Voss et al 1996;Nair 1998). Fumonisins could cause equine leukoencephalomalacia and porcine pulmonary oedema, as well as hepatocarcinomas and cholangiocarcinomas in rats (Voss et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Fumonisins could cause equine leukoencephalomalacia and porcine pulmonary oedema, as well as hepatocarcinomas and cholangiocarcinomas in rats (Voss et al 1996). These toxins are also potential human carcinogens because of the exceptionally high incidences of oesophageal cancer coincidentally found in areas of southern Africa (Marasas et al 1988) and China (Yang 1980;Cheng et al 1985) where F. moniliforme-contaminated corn is consumed as a dietary staple (Voss et al 1996). It has been demonstrated that fumonisins are hepatotoxic, nephrotoxic, atherogenic, immunosuppressive and embryotoxic in various experimental animal models (Nair 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Diseases induced by mycotoxins cause acute, chronic, and subchronic toxicities, which depend on different factors such as the animal species, age, sex, strain, dosage, and administration route (18,41). Fumonisins have been associated with different kinds of mycotoxicoses in domestic animals, such as leukoencephalomalacia in equines (34), pulmonary edema in pigs (10), and hepatocellular carcinoma in rats (15).…”
mentioning
confidence: 99%